Bioprinting of an osteocyte network for biomimetic mineralization. (28th July 2020) - Yang, Yiqi; Wang, Minqi; Yang, Shengbing; Lin, Yixuan; Zhou, Qinghui; Li, Hanjun; Tang, Tingting
Abstract: Osteocytes, essential regulators of bone homeostasis, are embedded in the mineralized bone matrix. Given the spatial arrangement of osteocytes, bioprinting represents an ideal method to biofabricate a 3D osteocyte network with a suitable surrounding matrix similar to native bone tissue. Here, we reported a 3D bioprinted osteocyte-laden hydrogel for biomimetic mineralization in vitro with exceptional shape fidelity, a high cell density (10 7 cells per ml) and high cell viability (85%–90%). The bioinks were composed of biomimetic modified biopolymers, namely, gelatine methacrylamide (GelMA) and hyaluronic acid methacrylate (HAMA), with or without type I collagen. The osteocyte-laden constructs were printed and cultured in mineralization induction media. After 28 d, increased dendritic cell connections and enhanced mineralized matrix production were observed after the addition of type I collagen. These results were further confirmed by the expression of osteocyte-related genes, markers of osteocyte morphology (Connexin43 and E11/Podoplanin), markers of mineralization (dentin matrix acidic phosphoprotein 1 (Dmp1)) and the cellular response to parathyroid hormone (PTH). Moreover, the 3D bioprinting constructs outperformed the 2D monolayer culture and they were at least comparable to 3D casted hydrogels in mimicking the natural osteocyte phenotype. All results indicated that the 3D bioprinting osteocyte network shows promise for mechanistic studies and pharmaceutical screening in vitro .